Desain Antena Yagi LTE - Ninda Febtaria; Rizadi Sasmita Darwis (Politeknik Caltex Riau, 2021)
In rural areas, an antenna is needed so that the LTE network can reach farther areas, making it easier for people to get information from the internet. Yagi antenna is the right antenna because it has a directional radiation pattern so that the direction of the beam is directional and effective for reaching long distances. In this research, the yagi antenna is designed and made to operate at 450 MHz LTE frequency. The design of this LTE yagi antenna uses a microstrip antenna as its driven element with FR4 substrate type and a relative permittivity value of 4.6. The material used for the reflector and director elements is aluminum with an outer diameter of 8 mm and an inner diameter of 7 mm. The LTE yagi antenna is designed to have 10 elements consisting of 1 reflector element, 1 driven element and 8 director elements. The parameters obtained from the simulation results of the Yagi LTE antenna have reached the target. The return loss at 450 MHz is -32.26 dB with VSWR 1.05 and gain 9.999 dBi. The radiation pattern of the simulated antenna horizontally and vertically are directional. The simulated antenna bandwidth has met the uplink and downlink frequencies. Keywords: Yagi Antenna, LTE, Microstrip Antenna.